Perforated peptic ulcer during the puerperium - Reyna-Villasmil, Eduardo (2023)
Peptic ulcer is less frequent in pregnant women than in non-pregnant women.Although it rarely perforates during pregnancy and even less frequently during thepuerperium, it is associated with an increased risk of maternal death. The use of nonsteroidalanalgesic and Helicobacter pylori infection are related to its pathogenesis.Due to its clinical features during pregnancy, puerperal sepsis and paralytic ileusmay delay diagnosis. After delivery, clinical signs such as new-onset tachycardia,abdominal pain, and increased distension should suggest the diagnosis. Sincecomplications can cause significant morbidity and mortality during the puerperium,early detection and prompt treatment are imperative. Treatment of perforatedpeptic ulcer during the puerperium is the same as for an urgent abdominalsurgical situation. Successful repair with omental patching usually seals the defectand prevents additional perforations. A case of perforated peptic ulcer during thepuerperium is presented.